Autobiographical narratives relate to Alzheimer's disease biomarkers in older adults. (October 2014) - Buckley, Rachel F.; Saling, Michael M.; Irish, Muireann; Ames, David; Rowe, Christopher C.; Villemagne, Victor L.; Lautenschlager, Nicola T.; Maruff, Paul; Macaulay, S. Lance; Martins, Ralph N.; Szoeke, Cassandra; Masters, Colin L.; et al.
ABSTRACT Background: Autobiographical memory (ABM), personal semantic memory (PSM), and autonoetic consciousness are affected in individuals with mild cognitive impairment (MCI) but their relationship with Alzheimer's disease (AD) biomarkers are unclear. Methods: Forty-five participants (healthy controls (HC) = 31, MCI = 14) completed the Episodic ABM Interview and a battery of memory tests. Thirty-one (HC = 22, MCI = 9) underwent β-amyloid positron emission tomography (PET) and magnetic resonance (MR) imaging. Fourteen participants (HC = 9, MCI = 5) underwent one imaging modality. Results: Unlike PSM, ABM differentiated between diagnostic categories but did not relate to AD biomarkers. Personal semantic memory was related to neocortical β-amyloid burden after adjusting for age and apolipoprotein E (APOE) ɛ4. Autonoetic consciousness was not associated with AD biomarkers, and was not impaired in MCI. Conclusions: Autobiographical memory was impaired in MCI participants but was not related to neocortical amyloid burden, suggesting that personal memory systems are impacted by differing disease mechanisms, rather than being uniformly underpinned by β-amyloid. Episodic and semantic ABM impairment represent an important AD prodrome.